PENGARUH PENGGUNAAN FREE SMARTPHONE SEBAGAI SUMBER BELAJAR SISWA DALAM MATA PELAJARAN PPKN TERHADAP HASIL BELAJAR SISWA KELAS X SMAN 8 PEKANBARU TA 2015/2016 - ', Novriyanti P; ', Gimin; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the problems that arise from the observations made by the researcher that is the community's consumption of technology makes the world of technology increasingly popular among students of one of the high-tech communication and computer-like functions is Smartphone, the phenomenon of smartphone use in the students, there are two main factors in Its use is the factor of need and lifestyle. The purpose of this research is to know the use of smartphone (intensity of exploiting, ease of access, and browsing tool) to know student learning result using smartphone and influence smartphone usage as learning resource to student learning result. Grand theory used for variable use of Smartphone Istiyanto (2013) and Munir (2014) while for student learning result variable suprijono (2013). This research method using quantitative descriptive analysis, the data in the analysis using simple linear regression. Based on the result of the research, it can be concluded that the percentage of respondents' responses to the use of free smartphones (Variable X) for the intensity of social network utilization is 91.03%, the intensity of web browsing utilization is 84.62%, for ease of accessing social network of 96, 15%, for ease of accessing web browsing for 87.18% this shows free smartphone usage as student learning resource in PPKn subject very good based on yardstick in range 75,01% - 100%. Based on the results of research, easy to find information, access teaching materials, journals and other tasks from Web browsing and Social network internet access so that the government provides internet network in various areas so that teachers can use to improve the learning process as a source of student learning.Keyword: Use of free smartphones, result learning